2009
DOI: 10.1016/j.urology.2008.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Hot Flashes During Androgen Deprivation Therapy With Luteinizing Hormone-Releasing Hormone Agonist Combined With Steroidal or Nonsteroidal Antiandrogen for Prostate Cancer

Abstract: Objectives:We conducted a prospective, randomized study to investigate hot flashes and quality of life (QOL) during combined androgen blockade (CAB) therapy using steroidal or nonsteroidal antiandrogens. Methods:A total of 151 patients with prostate cancer, enrolled into this study between May 2001and June 2003, were randomized to receive CAB therapy using an LHRH agonist (leuprorelin) combined with a steroidal antiandrogen (chlormadinone) or a nonsteroidal antiandrogen (bicalutamide). The incidence of, freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…In spite of low total sleep time, normal functioning was indicated by findings of circadian rhythmicity in activity levels and patient-reported general quality of life. Current reports of general quality of life appear consistent with previous androgen deprivation therapy studies (Joly et al 2006;Arai et al 2008;Sakai et al 2009). Conversely, clinically significant daytime sleepiness was reported by 23% of participants, and actigraphy results suggest that participants were napping during the day.…”
Section: Discussionsupporting
confidence: 88%
“…In spite of low total sleep time, normal functioning was indicated by findings of circadian rhythmicity in activity levels and patient-reported general quality of life. Current reports of general quality of life appear consistent with previous androgen deprivation therapy studies (Joly et al 2006;Arai et al 2008;Sakai et al 2009). Conversely, clinically significant daytime sleepiness was reported by 23% of participants, and actigraphy results suggest that participants were napping during the day.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, androgen deprivation therapy (ADT) for prostate cancer is highly associated with insomnia, potentially as a consequence of an increased occurrence of hot flushes and night sweats [77,78]. Although rare, oestrogen therapy is an effective therapeutic for ADT-induced hot flushes [79][80][81]. However, it is unknown whether oestrogen therapy is effective in improving sleep quality (but see [82]) in androgen-deprived men.…”
Section: (C) Sex Steroids Influence Sleepmentioning
confidence: 99%
“…As cyproterone is a recognised treatment in prostate cancer, and its use could interfere with hormonal therapy, medroxyprogesterone could be considered to be the standard treatment for hot flushes in men undergoing androgen suppression for prostate cancer. In Japan, Sakai et al [12] undertook a prospective, randomized study to longitudinally examine the status of the development of hot flushes in, and quality of life of, Japanese patients with prostate cancer who underwent combined androgen blockade (CAB) with a steroidal or nonsteroidal antiandrogen. They reported that the median frequencies of hot flushes daily were 1.3 and 2.2 for warmth/ flushing ( P =0.16) and 1.0 and 3.6 for sweating ( P =0.021) in the chlormadinone and bicalutamide groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The results for cyproterone acetate, which accounted for only a fifth of the evidence, appeared slightly unfavorable to MAB (5-year survival, 15.4% with MAB vs. 18.1% with androgen suppression [AS] alone; difference, −2.8% [standard error {SE}, 2.4]; log-rank, P =0.04 adverse), whereas those for nilutamide and flutamide appeared slightly favorable (5-year survival, 27.6% with MAB vs. 24.7% with AS alone; difference, 2.9% [SE, 1.3]; log-rank, P =0.005) [15]. Sakai et al [12] stated that, from the viewpoint of safety, chlormadinone, not cyproterone, was developed as a therapeutic drug for prostate cancer in Japan, but because their study had a limited duration of 2 years, the difference in survival time between the treatment groups was not assessed. Against such a background, we carried out gradual decrease of dose of CMA to avoid disadvantageous effects for prostate cancer treatment.…”
Section: Discussionmentioning
confidence: 99%